2004
DOI: 10.3732/ajb.91.9.1312
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast small heat‐shock proteins protect photosynthesis during heavy metal stress

Abstract: Plants can accumulate heavy metals when exposed to them at high levels. These metals can interfere with photosynthesis. Limited evidence suggests that increased synthesis of some heat-shock proteins (Hsps) may be a general plant response to metal stress, but the specific functions or structures protected by Hsps remain unidentified. Chloroplast small Hsps (smHsps) protect photosynthetic electron transport (Ph(et)) during heat, oxidative, and photoinhibitory stress, but it is not known if chloroplast smHsps are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Plants are often exposed to drastically changing temperatures, daily fluctuations of low and high light intensities, and many other biotic and abiotic stresses (Heckathorn et al, 2004). A single phyletic line may diverge into a series of lineages that can adapt to rather different niches.…”
Section: Model Of the Eci Is Valuable To Study The Local Gene Adaptationmentioning
confidence: 99%
“…Plants are often exposed to drastically changing temperatures, daily fluctuations of low and high light intensities, and many other biotic and abiotic stresses (Heckathorn et al, 2004). A single phyletic line may diverge into a series of lineages that can adapt to rather different niches.…”
Section: Model Of the Eci Is Valuable To Study The Local Gene Adaptationmentioning
confidence: 99%
“…Plant tolerance and/or resistance to metallic stress can be associated with one or more mechanisms, such as: (i) the excretion of chelating compounds that reduce the availability of the metal in the soil or water; (ii) the exclusion of the metal through selective absorption of elements; (iii) the retention of the metal in roots, preventing its translocation to the aerial part; (iv) the chelation or sequestration of heavy metals by ligands, compartmentalization, biotransformation and mechanisms of cellular repair; (v) the development of enzymes tolerant to the metal (Hall, 2002;Cobbett and Goldsbrough, 2002;Patra et al, 2004); (vi) the increase of production of intracellular compounds linked to the metal (Sharma and Dietz, 2006); (vii) the immobilization of the metal in the cellular wall (Cosio et al, 2005); (viii) homeostatic cellular mechanisms to regulate the concentration of metal ions inside the cell (Benavides et al, 2005); (ix) induction of heat-shock proteins (Heckathorn et al, 2004); (x) release of phenols from roots (Jung et al, 2003); (xi) the increase of tolerance to mineral deficiency or the decrease of nutritional requirements; (xii) the increase in absorption of certain macronutrients; and (xiii) the development of the capacity to absorb and to use minerals in the presence of heavy metals (Meda et al, 2007). As a result of these tolerance and/or resistance mechanisms (alone or in combination), some plants can grow in environments contaminated with metals where other species do not survive (Hall, 2002).…”
Section: Mechanisms Of Resistance or Tolerance To Metals In Plantsmentioning
confidence: 99%
“…However, the specific functions or structures protected by HSPs remain unknown. Heckathorn et al (2004) reported that the chloroplast small HSP, which function is to protect photosynthesis during heavy metal stress in corn leaves (Zea mays), were trigged by heavy metal. Previous studies have shown that most of the CeO 2 NPs taken by plants remain in the nanopariculate form; thus, it is possible that some of the NPs present in corn leaves reached the chloroplast affecting the HSP70 expression.…”
Section: Hsp 70 Analysismentioning
confidence: 99%